WHY DOES HOMELESS GOVERNANCE IS NOT WORKING IN LOCAL GOVERNMENT? - Alifa, Ripdah; 'Arif, Alma (Moestopo International Review on Social, Humanities, and Sciences, 2024)
The number of homeless in Tangerang Regency is the highest in Banten province, so a government commitment is needed to control the high number of homeless in Tangerang Regency. This study aims to identify and describe the factors that cause the governance of homelessness prevention in Tangerang District not to be optimal by using the constructivism paradigm that relies on qualitative data with an inductive approach. The data analysis technique used is thematic analysis with the coding method. The results of the study illustrate that the governance of homeless control in Tangerang Regency is still not running optimally. There are several factors affecting the homelessness governance is not working, namely the lack of human resources, lack of infrastructure, and lack of accredited LKSA by the Ministry of Social Affairs. The concept of governance is needed in controlling vagrancy so that the government plays a role in involving other actors in realizing good governance.